Development and Evaluation of a Problem-Based Learning E-LKPD for Environmental Change in Biology Learning - Wijaya, Ferbriani; Susila, Heni Rita; Pebriantika, Leni (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study was conducted in response to the need for innovative digital learning materials that can support active, contextual, and student-centered biology learning. Environmental change is a topic that requires students not only to understand scientific concepts, but also to analyze real-life problems related to environmental issues. Therefore, this study aims to develop and evaluate a Problem-Based Learning (PBL)-based Electronic Student Worksheet (E-LKPD) for environmental change material in Grade X biology. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed product was validated by material, instructional design, and media experts, and tested through one-to-one, small group, and field trials. The results showed that the E-LKPD achieved high validity, with scores of 87.84% from material experts, 86.23% from instructional design experts, and 84.76% from media experts, all categorized as valid with minor revisions. Practicality testing indicated very positive student responses, with scores of 89.40% in one-to-one evaluation and 90% in small group evaluation. The field test results, with an overall score of 91.48%, indicating that the E-LKPD significantly supports student engagement, motivation, and conceptual understanding. These findings suggest that integrating PBL into E-LKPD provides learning solution that promotes active learning and higher-order thinking skills. The developed E-LKPD is therefore suitable for implementation in biology learning and contributes to the advancement of technology-integrated education.